1985
DOI: 10.1080/03075078512331378716
|View full text |Cite
|
Sign up to set email alerts
|

The changing perspective of academic researchers, 1973–1983

Abstract: How has the approach of university teachers to research and their experience of it altered in a decade? This empirical study in aprovincial university notes continuities and differences in staff motivation towards research, the pressures they are under and the extent of their satisfaction with it.Academics continue to place intrinsic enjoyment and interest at the centre of their own motivation. However, their approach now more often implies a commitment to the notion that university teachers have a duty to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This recommendation has also been identified by a number of authors as one way of reducing the "widening gap between academic ideals and institutional realities" (cf. Fenker, 1975;Powell, Barrett & Shanker, 1983;Creswell, 1985;Startup, 1985;Everett and Entrekin, 1987).…”
Section: Importance Of Individual Autonomy In Selecting Research Topicsmentioning
confidence: 99%
“…This recommendation has also been identified by a number of authors as one way of reducing the "widening gap between academic ideals and institutional realities" (cf. Fenker, 1975;Powell, Barrett & Shanker, 1983;Creswell, 1985;Startup, 1985;Everett and Entrekin, 1987).…”
Section: Importance Of Individual Autonomy In Selecting Research Topicsmentioning
confidence: 99%
“…Of great significance is that some faculty members have expressed preferences for either teaching or research -some preferred research to teaching, and others teaching to research (Tierney, 1997 ). Startup (1985) observed that sometimes faculty members engage in research for the primary motive of intrinsic enjoyment and interest. Now, it is important to characterise faculty members' time allocation to either research or teaching.…”
Section: Rationalementioning
confidence: 99%
“…There is consensus however, that faculty members are now concentrating more on research and publications due to the reward structure, which places strong emphasis on research productivity, with low priority for teaching, advising and on responsibilities for the counselling of students (Michalak and Friedrich, 1981;Startup, 1985;Massy and Zemsky, 1994;Milem et al, 2000).…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation